Melania & Michelle : first ladies in a new era - Vigil, Tammy (Red Lightning Books, 2019)
From their full lives pre-nomination to their attitudes while occupying the White House, Vigil builds careful and thoughtful portraits of Melania Trump and Michelle Obama that provide new appreciation for the how these women, and the first ladies that came before them, have shaped our country.